Immunohistochemical features of progesterone receptors expression of placental barrier in women with multiple pregnancies resulting from assisted reproduction - T. D. Zadorozhna; B. M . Ventskivsky; S. M. Kylyhevich; I. V. Poladich (Zaporozhye State Medical University, 2016)
Hormonal disorders are one of the main known causes of miscarriage and preterm birth in multiple pregnancies resulting from assisted reproductive technology (ART). Progesterone and the number of its receptors play an important role in the preservation and prolongation of pregnancy and it is the pressing issue of our time. The study of placentas, as the main site of synthesis of progesterone, has high informative potential and it is the most important diagnostic object, and information received by its research is essential for the full conclusion on the causes, mechanisms, close and long-term effects of multiple pregnancy pathology. Aim. The aim of our study was to investigate immunohistochemical features of placentas from women with dichorionic diamniotic twin pregnancies in spontaneous fertilization and after use of assisted reproductive technology (ART). Methods and results. According to this goal we examined 94 women, 44 of whom had multiple pregnancies due to ART, 42 with separate multiple pregnancy and 38 women with a singleton pregnancy. We carried out clinical and statistical analysis of the course of pregnancy and childbirth in the studied groups. During the study it was found that multiple pregnancies due to assisted reproduction belong to the high risk of gestation, at which premature births occur much more frequently than in singleton pregnancies. We were the first to carry out the immunohistochemical study of placentas in which the highest expression of progesterone receptors in the nuclei of cells of decidua (45%) related to the parent structure of the placenta from women with multiple pregnancies caused by ART is found. It is also found that with increasing gestational age, there has been a significant decrease in the expression of the activity of progesterone receptors (from 45 to 2.5%), regardless of the method of conception and the number of fetuses. Conclusions. The results of the study point to the definitive link of structures of placental-endometrial relations as an important component of the appropriateness of hormone therapy.